Into the mirror : The Untold Story of Mukhtar Mai - Curran, Bronwyn (Quetta Gosha-e-Adab, 2007)
On the life and trials thereafter of Mukhtar Mai, rape victim from Pakistan
Include Acknowledgment
Keywords: Rape victims -- Mai, Mukhtar -- Sex discrimination against women